2018
DOI: 10.3389/fimmu.2018.02977
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs and Their Emerging Roles in Immune Regulation

Abstract: Circular ribonucleic acid (RNA) molecules (circRNAs) are covalently closed loop RNA molecules with no 5′ end caps or 3′ poly (A) tails, which are generated by back-splicing. Originally, circRNAs were considered to be byproducts of aberrant splicing. However, in recent years, development of high-throughput sequencing has led to gradual recognition of functional circRNAs, and increasing numbers of studies have elucidated their roles in cancer, neurologic diseases, and cardiovascular disorders. Nevertheless, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 92 publications
0
65
0
Order By: Relevance
“…Several circRNAs show clear evolutionary conservation or strict regulation function, implying that they are of functional importance. [14][15][16] The aberrant expression of circRNA has been found in a wide variety of tumors, including GM. [10][11][12][13] For example, Lei et al 17 revealed that hsa_circ_0076248 could promote GM tumorigenesis through sponging miR-181a and regulate SIRT1 expression.…”
Section: Circ-pitx1 Facilitates Cell Progression By Affecting Mir-5mentioning
confidence: 99%
“…Several circRNAs show clear evolutionary conservation or strict regulation function, implying that they are of functional importance. [14][15][16] The aberrant expression of circRNA has been found in a wide variety of tumors, including GM. [10][11][12][13] For example, Lei et al 17 revealed that hsa_circ_0076248 could promote GM tumorigenesis through sponging miR-181a and regulate SIRT1 expression.…”
Section: Circ-pitx1 Facilitates Cell Progression By Affecting Mir-5mentioning
confidence: 99%
“…Therefore, circRNAs can participate in the development and progression of different immune responses and immune diseases [23,24,114]. On the basis of the current studies, the majority of circRNAs defined in autoimmune diseases are ecircRNAs, and a few are ciRNAs and eIciRNAs [23,24,[114][115][116]. The circRNAs identified to date, their functions, and roles in immunological diseases are shown in Table 3.…”
Section: The Role Of Circrnas In Immune Regulationmentioning
confidence: 97%
“…In addition, researchers have found that CDR1as including exosomes inhibit miR-7-induced growth in recipient cells [22]. Testesspecific circRNA/circSry [the circular transcript of sex determining region Y (Sry) gene] can also serve as a sponge for miRNA-138 [23]. It contains 16 MREs of miRNA-138 and regulates the expression of miR-138-target genes, functioning similar to CDR1as [17].…”
Section: Circrnas Can Act As Mirna Spongesmentioning
confidence: 99%
See 2 more Smart Citations